Transformasi Ekonomi Kreatif Industri Minyak Pijat Rumahan: Perspektif Etika Bisnis Islam - Abdul Sumarlin; Astuty Hasti (LPPM Institut Pendidikan Nusantara Global, 2026)
Indonesia's creative economy industry is showing rapid growth, especially in the small and medium-sized enterprise (SME) sector, which plays an important role in the national economy. However, the development of creative MSMEs still faces various obstacles, such as limited capital, low-quality human resources, limited product innovation, and ineffective marketing strategies. Islamic ethical principles, such as honesty in communicating product benefits and a focus on business blessings, encourage both brands to transform while maintaining quality, transparency, and consumer trust as the basis for business decision-making. This study aims to analyze the creative economy transformation strategies of the Cap Pendekar and Cap Anoa home-based massage oil industries, emphasizing the implications of Islamic business ethics as a basis for business management. The research method used was a qualitative comparative case study approach. Data were obtained through in-depth interviews with business owners, workers, resellers, consumers, and supporting communities. The results indicate that Cap Pendekar still relies on a semi-manual production system with testimonial-based promotions and simple social media platforms, thus facing limitations in production capacity, innovation, and competitiveness in local and regional markets. In contrast, Cap Anoa has successfully developed a modern business strategy through branding based on local wisdom, product innovation, attractive packaging, digital media utilization, and a hybrid distribution system that reaches a wider consumer base. The analysis based on Islamic business ethics shows that both businesses have strived to implement the principles of monotheism, justice, responsibility, trustworthiness, and honesty. However, Cap Anoa has been more consistent in integrating these principles into a modern, adaptive and competitive business strategy. This study concludes that strengthening innovation-based creative economic strategies, digital marketing, and branding needs to be combined with the application of Islamic business ethics to enable traditional home industries to compete sustainably, fairly, and bring blessings to both the entrepreneurs and the community.